Srategi Komunikasi Pemasaran Digital Kelas Olah Wicara Anak Melalui Feed instagram @kowa_story - Novita, Weni (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
Children's speech class is one of the services that can help children improve their speaking and communication skills. Kowa is one of the non-formal education platforms that provides material on public speaking specifically for children, in order to attract public interest, the right digital marketing communication strategy is needed.The purpose of this study is to find out how the digital marketing communication strategy for children's speech classes through the @kowa_story Instagram feed. The method used in this research is Krippendorff's content analysis which is carried out through digital observation on the @kowa_story Instagram account from September 30, 2023 to December 31, 2023. The results of this study indicate that children's speech classes carry out more digital marketing communication strategies through the @kowa_story Instagram feed which are dominated by Public Relations and Publicity.